Antifibrotic Effect of Ethanolic Extract of Nerium indicum Mill. Standardized 5α-Oleandrin on Keloid Fibroblasts Cells - Mae Sri Hartati Wahyuningsih; Fara Silvia Yuliani; Dwiki Yuliya Rahmawati; Annisa Nurul Pratiwi (Faculty of Pharmacy, Universitas Gadjah Mada, 2018)
Keloid is a skin lesion caused by an abnormal proliferation of fibroblasts and the deposition of collagen in the wound healing process. Therapy for keloids is relatively limited and mostly has side effects. Recent studies show that 5α-oleandrin from N. indicum Mill. (N. indicum) has anti-keloid effect by inhibiting (proliferation, migration activity and TGF-β1 expression) keloid fibroblast. Further studies with N. indicum extract standardized 5α-oleandrin should be conducted to develop it as an anti-keloid agent by performing at proliferative effects, collagen accumulation, and keloid fibroblast migration. The antifibrotic activity of N. indicum extract on the proliferation of keloid fibroblasts was measured by MTT assay, whereas collagen deposits were observed by Sirius Red method. Observation of keloid fibroblast migration by scratch assay is according to Liang et al. (2009). Ethanol extract of N. indicum standardized 5α-oleandrin can inhibit the proliferation of keloid fibroblas with IC50 0.458 μg/mL, also inhibited collagen deposits with IC50 0.055 μg/mL at incubation for 72 hours. In incubation 48 hours after treatment with ethanol extract of 1.0 μg/mL occurred inhibition of migration significantly compared with control.